Identification of placental androgen receptor isoforms in a sheep model of maternal allergic asthma. (15th January 2021) - Meakin, Ashley S.; Morrison, Janna L.; Bradshaw, Emma L.; Holman, Stacey L.; Saif, Zarqa; Gatford, Kathryn L.; Wallace, Megan J.; Bischof, Robert J.; Moss, Timothy J.M.; Clifton, Vicki L.
Abstract: Maternal asthma is known to impact intrauterine growth outcomes, which may be mediated, in part, by altered androgen signalling. Our aim was to explore whether the sheep placenta expresses androgen receptor (AR) isoforms and determine if the differential expression of AR protein isoforms is altered by maternal asthma. Four known AR isoforms were detected (AR-FL, AR-v1, AR-v7, and AR-45), and their expression and subcellular distribution was altered in the presence of maternal allergic asthma. These findings underscore the importance for in vivo models of maternal asthma to delineate molecular patterns that may contribute to feto-placental growth and development. Highlights: Sheep placenta contains 4 characterised androgen receptor (AR) isoforms (AR-FL, AR-v1, AR-v7 and AR-45) that vary in expression in the presence of maternal allergic asthma and placentome type. Altered subcellular distribution of AR-45, AR-FL and AR-v1 isoforms in the presence of maternal asthma varies between placentome types. Changes in AR protein isoform expression and subcellular distribution between placentome types, in the presence and absence of maternal asthma, may contribute to altered placental physiology and fetal growth and development.